What is the general solution of the differential equation: $\left( {y\ln y} \right)dx - xdy = 0?$
Answer
Verified
442.8k+ views
Hint:The given differential equation can be solved by separable method, in which we separate variables and integrate them. Also to integrate one of the integrals use substitution method and then to get an explicit general solution, take both side anti logarithms (or exponential to the power e).
Complete step by step solution:
To find the general solution of the given differential equation: $\left(
{y\ln y} \right)dx - xdy = 0$, we will use a separation method, as we can see this is a type of separable differential equation.
As the differential equation $\left( {y\ln y} \right)dx - xdy = 0$ is a separable differential equation, separating the variables in it as follows
$
\Rightarrow \left( {y\ln y} \right)dx - xdy = 0 \\
\Rightarrow \left( {y\ln y} \right)dx = xdy \\
\Rightarrow \dfrac{{dx}}{x} = \dfrac{{dy}}{{\left( {y\ln y} \right)}} \\
$
We have separated the variables, now integrating both sides, we will get
\[ \Rightarrow \int {\dfrac{1}{x}dx} = \int {\dfrac{1}{{\left( {y\ln y} \right)}}} dy\]
As we can see the left hand integral is trivial but the right hand side integral is unsetting, so we will try a substitution method to simplify it.
Let us take $u = \ln y \Rightarrow du = \dfrac{1}{y}dy$
Substituting this in above integral, we will get
\[ \Rightarrow \int {\dfrac{1}{x}dx} = \int {\dfrac{1}{u}du} \]
Now we can integrate it easily,
\[ \Rightarrow \ln x + c = \ln u\]
Using property of log, we can also write it as
\[
\Rightarrow \ln x + \ln {\text{C}} = \ln u \\
\Rightarrow \ln {\text{C}}x = \ln u \\
\]
After restoring the substitution, we will get
\[ \Rightarrow \ln {\text{C}}x = \ln (\ln y)\]
Now taking exponential to base e, both sides, we will get
\[
\Rightarrow {e^{\ln {\text{C}}x}} = {e^{\ln (\ln y)}} \\
\Rightarrow {\text{C}}x = \ln y \\
\]
Again taking exponential to base e, we will get
\[
\Rightarrow {e^{{\text{C}}x}} = {e^{\ln y}} \\
\Rightarrow {e^{{\text{C}}x}} = y \\
\Rightarrow y = {e^{{\text{C}}x}} \\
\]
So \[y = {e^{{\text{C}}x}}\] is the general solution for the differential equation $\left( {y\ln y} \right)dx - xdy = 0$
Note: We have calculated the explicit general solution in this problem. Explicit solutions consist of dependent variables at the left hand side with power one and every other terms on the right hand side, whereas every solution which is not explicit is an implicit solution.
Complete step by step solution:
To find the general solution of the given differential equation: $\left(
{y\ln y} \right)dx - xdy = 0$, we will use a separation method, as we can see this is a type of separable differential equation.
As the differential equation $\left( {y\ln y} \right)dx - xdy = 0$ is a separable differential equation, separating the variables in it as follows
$
\Rightarrow \left( {y\ln y} \right)dx - xdy = 0 \\
\Rightarrow \left( {y\ln y} \right)dx = xdy \\
\Rightarrow \dfrac{{dx}}{x} = \dfrac{{dy}}{{\left( {y\ln y} \right)}} \\
$
We have separated the variables, now integrating both sides, we will get
\[ \Rightarrow \int {\dfrac{1}{x}dx} = \int {\dfrac{1}{{\left( {y\ln y} \right)}}} dy\]
As we can see the left hand integral is trivial but the right hand side integral is unsetting, so we will try a substitution method to simplify it.
Let us take $u = \ln y \Rightarrow du = \dfrac{1}{y}dy$
Substituting this in above integral, we will get
\[ \Rightarrow \int {\dfrac{1}{x}dx} = \int {\dfrac{1}{u}du} \]
Now we can integrate it easily,
\[ \Rightarrow \ln x + c = \ln u\]
Using property of log, we can also write it as
\[
\Rightarrow \ln x + \ln {\text{C}} = \ln u \\
\Rightarrow \ln {\text{C}}x = \ln u \\
\]
After restoring the substitution, we will get
\[ \Rightarrow \ln {\text{C}}x = \ln (\ln y)\]
Now taking exponential to base e, both sides, we will get
\[
\Rightarrow {e^{\ln {\text{C}}x}} = {e^{\ln (\ln y)}} \\
\Rightarrow {\text{C}}x = \ln y \\
\]
Again taking exponential to base e, we will get
\[
\Rightarrow {e^{{\text{C}}x}} = {e^{\ln y}} \\
\Rightarrow {e^{{\text{C}}x}} = y \\
\Rightarrow y = {e^{{\text{C}}x}} \\
\]
So \[y = {e^{{\text{C}}x}}\] is the general solution for the differential equation $\left( {y\ln y} \right)dx - xdy = 0$
Note: We have calculated the explicit general solution in this problem. Explicit solutions consist of dependent variables at the left hand side with power one and every other terms on the right hand side, whereas every solution which is not explicit is an implicit solution.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE